An objective analysis of drivability for two wheeler powertrain with control oriented dynamic model - Das,HB; Evangelou,SA; Dhinagar,SJ (2015)
The objective of this work is to estimate drivability characteristics parameters of two wheeler powertrain with control oriented powertrain model. The evaluation is essential for defining drivability characteristics for a future electric variable transmission (EVT) powertrain. The mathematical model for the complete powertrain is developed using suitable modeling approaches for the different sub-modules of the complete system. The Spark Ignition (SI) engine model used for this work is developed from mean value model approach and experimentally validated with test data from TVS Motor Company, India. The model is integrated with two types of transmission models, Continuous Variable Transmission (CVT) and Manual Transmission (MT). It simulates dynamic power-flow from the engine to wheel for analyzing longitudinal drivability of the vehicle for both powertrain configurations. It is proposed that the drivability can be measured with certain parameters which show good correlation with subjective assessments for vehicle launch as well as tip in condition. The objective assessment of both types of powertrains is performed using the above mentioned powertrain models. The results of the simulation for drivability tests are discussed in this paper.